Efficacy of 5-nitroimidazoles for the treatment of giardiasis: a systematic review of randomized controlled trials. - Vinay Pasupuleti; Angel Arturo Escobedo; Abhishek Deshpande; Priyaleela Thota; Yuani Roman; Adrian V Hernandez (PLoS Neglected Tropical Diseases)
Background Giardiasis is one of the most common causes of diarrheal disease worldwide and 5-nitroimidazoles (5-NI) are the most commonly prescribed drugs for the treatment of giardiasis. We evaluated the efficacy of 5-nitroimidazoles (5-NI) in the treatment of giardiasis in a systematic review of randomized controlled trials (RCTs). Methodology/principal findings We conducted a comprehensive literature search in PubMed-Medline, Scopus, Web of Science and Cochrane Library for RCTs evaluating the efficacy of 5-NI vs. control (placebo or active treatment) on parasitological cure in patients with parasitologically-demonstrated giardiasis. The search was performed in May 2013 with no language restriction by two authors independently. The efficacy outcome was parasitological cure, and harmful outcomes were abdominal pain, bitter or metallic taste, and headache. We included 30 RCTs (n = 3,930). There was a significant and slightly higher response rate with 5-NI in giardiasis treatment (RR 1.06, 95%CI 1.02-1.11, p = 0.005). There was high heterogeneity among studies (I2 = 72%). The response rates for metronidazole, tinidazole and secnidazole were similar (RR 1.05, 95%CI 1.01-1.09, p = 0.01; RR 1.32 95%CI 1.10-1.59, p = 0.003; and RR 1.18 95%CI 0.93-1.449, p = 0.18, respectively). On subgroup analyses, the response rates did not vary substantially and high heterogeneity persisted (I2 = 57%-80%). Harmful outcomes were uncommon, and 5-NIs were associated with lower risk of abdominal pain, and higher risk of both bitter or metallic taste and headache. Conclusions Studies investigating the efficacy of 5-NI in giardiasis treatment are highly heterogeneous. 5-NIs have a slightly better efficacy and worse profile for mild harmful outcomes in the treatment of giardiasis in comparison to controls. Larger high quality RCTs are needed to further assess efficacy and safety profiles of 5-NI.